Determinants of ERM quality and its impact on company value - Hidayah, Nurul; Azhar, Zubir; Setiany, Erna; Utami, Wiwik; Tarmidi, Deden (Business: Theory and Practice, 2024)
Company value results from how well a company has managed its resources to achieve business benefits. However, there are always risks associated with conducting business, and effective risk management (ERM) can help reduce those risks so that they stay in the way of the entity’s performance goals. This study examines the factors that affect ERM quality, such as company size, auditor caliber, concentrated ownership, and director oversight, and how this affect business success. Purposive sampling produced a sample of 552-panel data used in this study’s research of manufacturing firms in Indonesia and Malaysia. With the aid of STATA software, this study discovered a favorable relationship between auditor quality and ERM and also impact firm size, auditor quality, concentrated ownership, and ERM on company value. The expansion test revealed that while the quality of auditors in Malaysian companies had a positive effect on firm value while those in Indonesia did not, and vice versa, the quality of auditors in Indonesian companies had a stronger positive effect on ERM quality than the quality of auditors in Malaysian companies. In contrast to businesses in Malaysia, monitoring of directors has a beneficial impact on a company’s worth in Indonesia.